Üniversite Öğrencilerinin Dijital Ortamda Sağlık Bilgisi Edinme ve Teyit Davranışları ile Siberkondri Ciddiyet Düzeyi Arasındaki İlişki: Kesitsel Araştırma. - ÇATAN İNAN, Funda; Nur ALLAH VERDİ, Saide (Turkiye Klinikleri Journal of Medical Sciences)
Objective: As internet usage continues to rise, individuals increasingly engage in seeking health-related information online, which in turn has been associated with higher levels of cyberchondria severity. This study aims to examine the relationship between cyberchondria severity and behaviors related to obtaining and verifying health information from digital media among university students. Material and Methods: This cross-sectional and analytical study was conducted between May and June 2024 with the participation of 521 students enrolled at Bilecik Şeyh Edebali University. Data were collected via an online questionnaire, which included sociodemographic items, the Turkish-adapted Cyberchondria Severity Scale, and Behaviors on Obtaining and Verifying Health Information from Digital Media Scale. Data analysis was performed using SPSS version 26.0, applying independent samples t-tests, one-way analysis of variance, Pearson chi-square test and Fisher's exact test (as appropriate), and Pearson correlation analysis. All results were evaluated at a 95% confidence interval with a significance level of p<0.05. Results: The findings revealed a positive and statistically significant relationship between cyberchondria severity and behaviors related to obtaining and verifying health information online (p<0.001). Students who used the internet and social media more frequently, and those who searched for health information before or after visiting a doctor, had higher levels of cyberchondria. The findings indicated that higher frequencies of health-related internet searches were associated with significantly higher cyberchondria subscale scores. Conclusion: Higher levels of cyberchondria among university students were associated with more frequent online health information obtaining and verification behaviors. These findings suggest that health-related anxiety may influence both information-obtaining and verification behaviors.